2018
DOI: 10.1016/j.jogoh.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Management of endometriosis

Abstract: First-line diagnostic investigations for endometriosis are physical examination and pelvic ultrasound. The second-line investigations are: targeted pelvic examination performed by an expert clinician, transvaginal ultrasound performed by an expert physician sonographer (radiologist or gynaecologist), and pelvic MRI. Management of endometriosis is recommended when the disease has a functional impact. Recommended first-line hormonal therapies for the management of endometriosis-related pain are combined hormonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 29 publications
0
47
0
1
Order By: Relevance
“…Endometriosis is a multifaceted gynecological condition with an estimated prevalence of ∼10-15% of the general population (1). It is histologically defined as the presence of glands and stroma of endometrial tissue outside the uterus, mainly in the peritoneal cavity and ovaries (2)(3)(4). Reports have shown the location of these lesions in sub-peritoneal fat, recto-vaginal or recto-uterine spaces, bowel, bladder, pelvic nerves, uterosacral ligaments, ureters, anterior abdominal wall, as well as abdominal skin, diaphragm, pleura, lungs, pericardium, and brain, although these locations are usually less frequent than in pelvic structures (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is a multifaceted gynecological condition with an estimated prevalence of ∼10-15% of the general population (1). It is histologically defined as the presence of glands and stroma of endometrial tissue outside the uterus, mainly in the peritoneal cavity and ovaries (2)(3)(4). Reports have shown the location of these lesions in sub-peritoneal fat, recto-vaginal or recto-uterine spaces, bowel, bladder, pelvic nerves, uterosacral ligaments, ureters, anterior abdominal wall, as well as abdominal skin, diaphragm, pleura, lungs, pericardium, and brain, although these locations are usually less frequent than in pelvic structures (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is defined as the presence of endometrial glands and stroma outside the uterus, which are commonly found in the peritoneal cavity and ovaries [ 1 3 ]. Endometriosis is the leading cause of chronic and cyclic pelvic pain in reproductive age women, affecting 10-15 % of women worldwide; pain symptoms include dysmenorrhea, dyspareunia, dysuria, and dyschezia [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combined hormonal contraceptives, are recommended as first-line therapy followed by analogs and antagonists of GnRh. In case of failure of the initial treatment, recurrence, or multiorgan involvement, a multidisciplinary surgery is recommended ( 10 ).…”
Section: Introductionmentioning
confidence: 99%